2016
DOI: 10.3748/wjg.v22.i46.10226
|View full text |Cite
|
Sign up to set email alerts
|

Genotype specific peripheral lipid profile changes with hepatitis C therapy

Abstract: AIMTo evaluate magnitude/direction of changes in peripheral lipid profiles in patients undergoing direct acting therapy for hepatitis C by genotype.METHODSMono-infected patients with hepatitis C were treated with guideline-based DAAs at a university-based liver clinic. Patient characteristics and laboratory values were collected before and after the treatment period. Baseline demographics included age, ethnicity, hypertension, diabetes, hyperlipidemia, treatment regimen, and fibrosis stage. Total cholesterol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…More recently, studies show an increase of TC and LDL levels during treatment with DAAs (17,18) , as we observed. Meissner et al (16) , and Mark et al (19) , also observed a decrease in TG serum levels, as we observed as well.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…More recently, studies show an increase of TC and LDL levels during treatment with DAAs (17,18) , as we observed. Meissner et al (16) , and Mark et al (19) , also observed a decrease in TG serum levels, as we observed as well.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the DELTA TC and DELTA LDL were higher in genotype 3 patients, although DELTA triglycerides were lower in genotype 1. Mark et al (19) , observed which DELTA cholesterol levels were higher in GTP 3 than in GTP 1 and 2 (0.028 and 0.019 respectively).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, HCV eradication by interferon‐based therapy reverses hypolipidemia, 5 and this results should also be found after therapy with direct‐acting antivirals (DAAs) 6–8 . Nevertheless, the results have not been consistent regarding certain lipid profiles across studies 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…HCV utilizes peripheral lipid metabolism pathways including hepatocyte very-low-density lipoprotein (VLDL) for viral assembly and requires several apolipoproteins for production of infective particles [3]. As a result, chronic hepatitis C (CHC) is associated with reduced total cholesterol, low-density lipoprotein (LDL) and apolipoprotein B (ApoB) levels as well as an increased rate of insulin resistance (IR) and type 2 diabetes mellitus [4].…”
Section: Introductionmentioning
confidence: 99%